2016
DOI: 10.3174/ajnr.a4773
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cerebral Adrenoleukodystrophy: MR Perfusion Measurements and Their Use in Predicting Clinical Outcome after Hematopoietic Stem Cell Transplantation

Abstract: Background and Purpose To prospectively measure MR perfusion (MRP) parameters in patients with cerebral adrenoleukodystrophy (cALD) pre- and post-hematopoietic stem cell transplantation (HSCT), and to correlate those measurements with the clinical outcome. Materials and Methods Ten cALD patients prospectively underwent DSC-MRP at <45 days pre-(baseline), 30–60 days post-, and 1 year post-HSCT. MRP measurements in the 10 patients and 8 controls were obtained from the parietooccipital WM (POWM), callosal splen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…As in prior studies, this study found that most children with pPRES have normal findings on the follow‐up neurologic examination, but this study's small number of patients precluded an adequate analysis for predictors of poor outcome 19,20 . Regarding DWI, reduced diffusion can be noted in 15‐20% of PRES, typically in the cortex‐subcortical WM, but did not occur in this study; reduced diffusion of the callosal splenium or PVWM did occur related to active demyelination or repair in the setting of cALD, as described previously 3,7,9,21 …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…As in prior studies, this study found that most children with pPRES have normal findings on the follow‐up neurologic examination, but this study's small number of patients precluded an adequate analysis for predictors of poor outcome 19,20 . Regarding DWI, reduced diffusion can be noted in 15‐20% of PRES, typically in the cortex‐subcortical WM, but did not occur in this study; reduced diffusion of the callosal splenium or PVWM did occur related to active demyelination or repair in the setting of cALD, as described previously 3,7,9,21 …”
Section: Discussionsupporting
confidence: 66%
“…Therefore, variations in the imaging appearance of these disorders could be multifactorial and related to the site of endothelial injury, severity, duration, or other exacerbating factors. Notably, regarding outcomes, preliminary studies of cALD have found that the initial sites of involvement on DTI/DWI and MR perfusion correlate with outcome, but involvement by pPRES was not accounted for, and thus this study's results are preliminary 18,21 …”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…( Schmid-Schönbein et al , 2001 ; Aubourg, 2015 ). Evidence of abnormal microvascular function in ALD patients includes: (i) ex vivo histopathology showing distorted microvascular permeability beyond the edge of the demyelinating lesions ( Musolino et al , 2015 ); (ii) in vitro experiments showing that lack of ABCD1 in human brain microvascular endothelial cell causes increased adhesion and permeability to leucocytes ( Musolino et al , 2015 ); and (iii) in vivo MRI demonstrating that contrast extravasation ( Loes et al , 2003 ) and white matter hypoperfusion predict lesion progression and clinical outcome after haematopoietic stem cell transplantation (HSCT) ( Musolino et al , 2012 ; McKinney et al , 2016 ). Magnetic resonance perfusion abnormalities have also been found to be associated with white matter lesion progression in other inflammatory demyelinating disorders, such as multiple sclerosis, optic neuritis, acute disseminated encephalomyelitis and progressive multifocal leukencephalopathy ( Khoury et al , 2013 ; Cramer et al , 2015 ; D'haeseleer et al , 2015 ; Hiremath et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%